2022
DOI: 10.1186/s12877-022-03338-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 vaccine uptake among French population aged 65 years and older: results from a national online survey

Abstract: Background In France, the increase in COVID-19 vaccine uptake among older adults slowed down between May and June 2021. Using the data from a national survey, we aimed to assess COVID-19 vaccine uptake among French residents aged 65 years and older, particularly at risk of severe form of the infection, and identify factors associated with non-vaccination. Methods A cross-sectional online survey collected the immunization status/intention to get the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A possible explanation for indicating the protection as the main reason is the extensive and persistent diffusion of SARS-CoV-2 infection that may have contributed to the awareness among the sample with a consequent high sense of urgency regarding this vaccination. Earlier studies in different geographic areas showed comparable results [8,[18][19][20]. Furthermore, only 22.6% of the respondents indicated that they were advised by a physician to get this booster dose.…”
Section: Discussionmentioning
confidence: 85%
“…A possible explanation for indicating the protection as the main reason is the extensive and persistent diffusion of SARS-CoV-2 infection that may have contributed to the awareness among the sample with a consequent high sense of urgency regarding this vaccination. Earlier studies in different geographic areas showed comparable results [8,[18][19][20]. Furthermore, only 22.6% of the respondents indicated that they were advised by a physician to get this booster dose.…”
Section: Discussionmentioning
confidence: 85%
“…This study has several limitations. Firstly, other potential drivers of COVID-19 vaccine non-uptake such as interpersonal, anthropological and social factors were not investigated in the present study 27,28,56 and this constitutes a main limitation of the study. Secondly, information on molecular typing of SARS-CoV-2 lineage found in fully vaccinated patients is lacking and this might have introduced interpretation bias.…”
Section: Discussionmentioning
confidence: 94%
“…The COVID-19 vaccination uptake was relatively low in the study, which is lower than that reported previously in Cameroon 24,25 and a global estimate of COVID-19 vaccination uptake rate reported by Zhang and colleagues 15 . Other studies reported higher vaccine uptake in specific groups such as elderly persons, college students and transborder populations [26][27][28] . Several factors drive the intention to accept, delay and abstain from vaccination and these include trust in vaccine approval, the perceived effectiveness of the vaccine for protecting others and conspiracy beliefs 29,30 .…”
Section: Discussionmentioning
confidence: 95%
“…Vaccine hesitancy in the older age group was commonly reported in different settings [21,66,67]. Despite this hesitancy, COVID-19 vaccination uptake was still high among the elderly population, especially nursing home residents or elderly people who are familiar with new technologies (e.g., online vaccination appointments, QR code for COVID-19 pass) [68].…”
Section: Indirect Effect On Vaccination In the General Populationmentioning
confidence: 99%